2022
DOI: 10.1039/d1dt03898b
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-small bimetallic phosphides for dual-modal MRI imaging guided photothermal ablation of tumors

Abstract: Metal phosphides have been proved to be the potential theranostic agents of tumor. However, the limitation of single-modal imaging or treatment effect of such materials need to be further improved....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Bimetallic nanoparticles have found numerous applications in medicine, including diagnostic (bio-imaging), therapy (cancer therapy) and preventive (antimicrobial, antioxidant, antidiabetic drug delivery) medicine (Table 3). The highly magnetic properties of Au-Fe and Ni-Co bimetallic nanoparticles makes them suitable to use as contrast agent for CT and MRI diagnosis/prognosis imaging [224] and theranostic agent for tumors [225]. Similarly, Cu-Fe have been used for enhanced chemodynamic therapy [226], Pd-Pt, Au-Co, Au-Co, Ag-Cu, Au-Pt have been used for cancer therapeutics and anticancer activity [21,[227][228][229][230] and Au-Bi have been used for the inhibition of tumor cells [231].…”
Section: Biological Applicationsmentioning
confidence: 99%
“…Bimetallic nanoparticles have found numerous applications in medicine, including diagnostic (bio-imaging), therapy (cancer therapy) and preventive (antimicrobial, antioxidant, antidiabetic drug delivery) medicine (Table 3). The highly magnetic properties of Au-Fe and Ni-Co bimetallic nanoparticles makes them suitable to use as contrast agent for CT and MRI diagnosis/prognosis imaging [224] and theranostic agent for tumors [225]. Similarly, Cu-Fe have been used for enhanced chemodynamic therapy [226], Pd-Pt, Au-Co, Au-Co, Ag-Cu, Au-Pt have been used for cancer therapeutics and anticancer activity [21,[227][228][229][230] and Au-Bi have been used for the inhibition of tumor cells [231].…”
Section: Biological Applicationsmentioning
confidence: 99%
“…In general, contrast agents are classified into positive (T 1 ) contrast agents that lead to the lesion looking bright, and negative (T 2 ) contrast agents that make the lesion dark. It has been observed that the signal from single-mode MRI often interferes, limiting the diagnosis; whereas T 1 -T 2 dual-modal contrast agents can generate comparative complementary images with the same in-plane geometries with different contrast, that facilitate great achievements in self-confirmed MRI detection with higher accuracy and precise diagnosis, 17,18 which is an active research area at the present time. Previously, we have examined multimodal theranostic efficiencies revealing good potency of PBNC in cancer therapy as well as in diagnosis with r 1 relaxivity of B5.14 mM À1 s À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal oxide (TMO) semiconductor nanomaterials have attracted wide attention in recent years for their superior biocompatibility, simple preparation, and regulable localized surface plasmon resonance (LSPR) effect. 13,14 Moreover, a lot of work has focused on the wide-band absorption of NIR TMO agents and their derivatives. 15–17 According to the previous reports by our group, 18,19 non-stoichiometric WO 3− x nanomaterials had strong 808 nm NIR absorption and possessed the LSPR effect.…”
Section: Introductionmentioning
confidence: 99%